PENGARUH PENERAPAN GOOD GOVERNANCE, SISTEM ADMINISTRASI PERPAJAKAN MODERN DAN RISIKO SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI YANG MELAKUKAN PEKERJAAN BEBAS - Erika Muliasari; Fadjar Harimurti; Suharno Suharno (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2020)
This study aims to analyze the effect of applying good governance, moderntax administration systems and the risk of tax sanctions on the compliance ofindividual taxpayers who do free work at KPP Sukoharjo. The research sample of100 individual taxpayers who do free work at KPP Pratama Sukoharjo. Samplingin slovin formula research with simple random sampling method. Testing is donewith your linear regression analysis tool. The results showed that theimplementation of good governance, modern tax administration system and therisk of tax sanctions have a significant effect on the compliance of individualtaxpayers who do free work.